Death anxiety and suicidal ideation in patients with alcohol use disorder - Çiçek, İsmet Esra (Journal of Dependence, 2021)
Objective: In this study, the death anxiety level of individuals with alcohol use disorder was compared with healthy controls and the relationship with suicidal ideation was evaluated. Method: Twenty-two patients diagnosed with alcohol use disorder and 20 healthy controls with similar sociodemographic characteristics were included in the study. Suicidal ideation and death anxiety were evaluated in the participants. Results: Death anxiety did not differ in individuals with alcohol use disorder compared to controls, and suicidal ideation was found to be high. Suicidal ideation and severity of alcohol use were found to be related. Conclusion: The level of death anxiety was not high in patients with alcohol use disorder. However, our findings suggest a potential link between alcohol use disorder and suicidal ideation and suicide attempt.Studies with larger samples are needed to evaluate death anxiety and related factors in individuals with alcohol use disorder..